The Effectiveness of Playing Footprints and Hands on Static Balance in Children Aged 4-6 Years with Flat Foot Conditions in TK Tunas Tridharma Plus Samarinda - Gyta Krisdiana Cahyaningrum; Naheria Naheria; Didik Cahyono; Ayu Aprilia Pangestu Putri (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
The aim of this research was to determine the effect of playing with footprints and hands on the static balance of children aged 4 - 6 years with flat feet at Tunas Tridharma Plus Kindergarten Samarinda. Research methods used is a quantitative approach with a pre-experimental research group design after testing. The population of this research is students Tunas Tridharma Plus Kindergarten Samarinda. The sample taken in this research used purposive sampling with as many respondents as possible 20 children. The data collection techniques used are observation, experimentation and documentation. The data analysis technique used is statistical analysis description, kolmogorov smirnov normality test and test paired sample test. Based on the research results, there are significant changes in abilities the child's static balance as shown by the results of the paired sample test as big as Sig. (2-tailed ) 0.001<0.05, so H0 is rejected and H1 is accepted, meaning that the effectiveness of the footprints and hands game has a significant influence on the static balance ability of children aged 4-6 years in flat foot conditions.